Do We Report the Information That Is Necessary to Give Psychology Away? A Scoping Review of the Psychological Intervention Literature 2000–2018. (January 2022) - Premachandra, Bharathy; Lewis, Neil A.
Psychologists are spending a considerable amount of time researching and developing interventions in hopes that their efforts can help to tackle some of society's pressing problems. Unfortunately, those hopes are often not realized—many interventions are developed and reported in journals but do not make their way into the broader world they were designed to change. One potential reason for this is that there may be a gap between the information reported in articles and the information others, such as practitioners, need to implement the findings. We explored this possibility in the current article. We conducted a scoping review to assess the extent to which the information needed for implementation is reported in psychological intervention articles. Results suggest psychological intervention articles report, at most, 64% of the information needed to implement interventions. We discuss the implications of this for both psychological theories and applying them in the world.